A more perfect heaven : how Nicolaus Copernicus revolutionized the cosmos - Sobel, Dava (Walker, 2011)
Traces the story of the reclusive sixteenth-century cleric who introduced the revolutionary idea that the Earth orbits the sun, describing the dangerous forces and complicated personalities that marked the publication of Copernicus's findings.